Authorizing the shogunate : ritual and material symbolism in the literary construction of warrior order - Selinger, Vyjayanthi R. (Vyjayanthi Ratnam) (Brill's Japanese studies library, 2013)
Authorizing the Shogunate is a study of the symbolic construction of warrior order in the Heike monogatari corpus.